Development of Home Health Services for Patients with Prostate, Kidney, and Adrenal Cancer in Türkiye - Fatih Göksel; Erdem Öztürk; Numan Yıkılmaz (Gazi Medical Journal)
Objective: Cancer detection rates are on the rise because of advances in technology, more widely used imaging methods, and the widespread implementation of screening tests. While the increase is more noticeable among early stage cancers, there has also been an increase in metastatic stage patients. This study evaluated the distribution of patients receiving home health care services (HHC) for urologic cancers, including prostate, kidney, and adrenal cancers, over the course of several years. Methods: This study evaluated the number of patients who received HHC services for prostate, kidney, and adrenal cancer between 2011 and 2017. The number of patient visits and service teams was also assessed. Results: This study evaluated the number of patients who received HHC services for prostate, kidney, and adrenal cancer between 2011 and 2017. The study found an increase in service teams, from 593 in 2011 to 662 in 2017, operating across 81 provinces in the country. Between 2011 and 2017, there was an increase in the number of patients diagnosed with urological malignancies, primarily prostate cancer. In 2011, 1,407 patients were treated, whereas in 2017, 13,007 patients were treated. The increase in this figure was attributed to improved diagnoses, heightened HHC awareness, and increased healthcare services. Conclusion: It is worth noting that urological malignancies are on the rise globally, and this trend is also observed in our country. Routine home visits for patients undergoing active or palliative treatment are crucial for the follow-up and seamless continuation of care. In this group of patients, particularly those in advanced stages, physical limitations and contact with other patients make it challenging to attend hospital appointments. As such, raising awareness is key to expanding access to a broader pool of patients.